Security analysis of ultralightweight RFID protocols - Aktaş, Serdar. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
RFID (Radio Frequency Identi cation) is a technology that uses radio waves as a medium to exchange data between a reader and an electronic tag for the purpose of object identi cation and tracking. RFID tags are considered as a replacement technology for barcodes and other means of traditional identi cation tools which traditionally nd applications in manufacturing, supply chain management and inventory control. Security and privacy aspects of RFID are becoming more important as RFID technology continues to ourish as an inherent part of virtually every ubiquitous environment. As the nodes of RFID systems mostly su er from low computational power and small memory size, strong cryptographic protocols are not appropriate for low-cost RFID tags. Therefore, designing security mechanisms for RFID systems turn out to be very challenging that many authentication protocols have been proposed recently by an increasing number of researchers. Nevertheless, it is shown that majority of these proposals do not provide security and privacy. The work done in this M.S. thesis is to analyze the privacy and security aspects of ultralightweight RFID protocols de ned in the previous literature and outline the weaknesses in these protocols. Also in a new ultralightweight RFID protocol we manage to attain a total breakdown by compromising the secret key information by revealing each bit using the weakness of XOR operation. Other weaknesses, we report for this ultralightweight RFID protocol include desynchronization, replay and traceability aws.
Keywords: Radio frequency identification systems -- Security measures.